The Influence of Product Quality, Service Quality and Price on Consumer Satisfaction at Hasanah Bakery Rantauprapat - Nur Ainun Lubis; Siti Lam’ah Nasution; Nova Jayanti Harahap (CV. AFDIFAL MAJU BERKAH, 2026)
The study aims to determine and analyze the effect of product quality, service quality, and price on consumer satisfaction at Hasanah Bakery Rantauprapat. The population in this study were consumers of Hasanah Bakery Rantauprapat, sample determination using the Lemeshow formula with Accidental Sampling technique totaling 96 respondents. The data collection technique used a questionnaire as a research instrument. This type of research is a descriptive questionnaire where the data was processed using SPSS 23. Data analysis using Instrument Test (Validity and Reliability), Classical Assumption Test in the form of Normality, Multicollinearity, Heteroscedasticity, Multiple Linear Regression, Hypothesis testing using the t-test and F-test and the Determination Coefficient Test. The results of the study showed that product quality had a positive and significant effect on consumer satisfaction with a t-value of 4.209> t-table 1.986 with a significance level of 0.000. Service quality has a positive and insignificant effect on consumer satisfaction with a t-value of 1.222 < t-table 1.986 and a significance level of 0.223. Price has a positive and significant effect on consumer satisfaction with a t-value of 3.813 > t-table 1.986 with a significance level of 0.000. Research results based on the simultaneous F-test of product quality, service quality, and price have a positive and significant effect on consumer satisfaction